Aetiology, Importance and Control of a Vine-Browning and Die-back Disease of Water Yam (Dioscorea Alata L.) in the Volta Region of Ghana - Coffie, S.A. (University of Ghana, 2013)
Vine-browning and die-back disease (anthracnose disease) is a major constraint and a predominant disease in all yam producing areas especially, in Africa. The disease reduces photosynthetic area of infected yam plants resulting in severe yield loss. Farmers and Agricultural Extension Agents in the Nkwanta-North and Krachi-West districts of the Volta Region have recently reported high incidence of the disease on their farms. A study was, therefore, conducted from January, 2012 to June, 2013 to assess farmers’ knowledge and perception of the disease and its economic impacts on their livelihoods, determine the incidence and severity of the disease, identify the causal organisms of the disease, characterize the strains of the pathogens inducing the disease, use tissue culture-derived whole-plant assay to screen water yam cultivars for anthracnose resistance and develop effective integrated pest management strategy for the disease in the field. Assessment of farmers’ knowledge and perception was ascertained through questionnaires and interviews of 120 D. alata farmers in the Nkwanta-North and Krachi-West districts of the Volta Region. The findings indicated that, most D. alata farmers in both districts were aware of the presence of a vine-browning and die-back disease in their fields and could identify it by its symptoms but were ignorant of its causal organisms, spread and control. The incidence and severity of the disease in the Nkwanta-North district (75.30% and 1.80) were higher compared to Krachi-West district (55.70% and 1.60). The pathogens responsible for the disease in the Volta region and other yam growing regions (Ashanti, Brong-Ahafo, Central, Eastern and Northern regions) in Ghana were confirmed as Colletotrichum gloeosporioides Penz. and Sacc. and C. truncatum Andrus and Moore using symptoms of the disease, morpho-cultural characteristics and genome analysis of isolates, and pathogenicity test. The vine-browning and die-back disease was identified as anthracnose disease of D. alata. Morpho-cultural characters and Polymerase Chain Reaction (PCR) with five Random Amplified Poly-Dimorphism (RAPD) primers (OPA-11, OPA-18, OPC-5, OPC-7 and OPC-16) and five Inter-Spacers Restriction Fragment Length Polymorphism (ITS-RFLP) enzymes (HhaI, HaeIII, HinfI, MspI and RsaI) were used to characterize 16 strains of C. gloeosporioides and four strains of C. truncatum obtained from diseased D. alata samples in the Volta Region and other five yam growing regions in Ghana (Ashanti, Brong-Ahafo, Central, Eastern and Northern). The 16 C. gloeosporioides strains clustered into two major groups (with similarity of 52%) and six sub-groups while the C. truncatum strains were put into two groups (with similarity of 30%) using unweighted pair-group method with arithmetic average (UPGMA). Screening of 12 D. alata cultivars for resistance to the disease was performed using tissue culture-derived whole-plant assay. Of the 12 cultivars, six (TDa008, TDa010, TDa014, TDa023, TDa025 and TDa027) were resistant to the disease but at varying levels whiles the six other cultivars (TDa007, TDa013, TDa015, TDa018, TDa019 and TDa021) were susceptible at varying levels. Cultivar TDa023 was highly resistant while TDa019 was highly susceptible. The use of integrated pest management strategy consisting of hot-water treated seed yam (45±1 o C for 20 minutes and drying for 30 minutes) of the highly resistant cultivar (TDa023) along with monthly weeding and Mancozeb sprays significantly (P < 0.05) reduced anthracnose severity (1.2) compared to the control (3.0) in the field. Although, the technology developed could effectively reduce the disease, it requires additional research at two or more locations to be sure of its sustainability before recommending to farmers. Moreover, benefit-cost analysis ought to be undertaken on the developed IPM strategy.
Thesis (MPHIL)-University of Ghana, 2013